2016
DOI: 10.14238/sp15.5.2014.281-8
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko yang Berperan pada Mortalitas Sepsis

Abstract: Latar belakang. Sepsis merupakan penyebab utama kematian bayi dan anak. Status imun pejamu dan malnutrisi merupakan faktor penting yang menentukan luaran pada sepsis. Skor pediatric logistic organ dysfunction (PELOD) adalah sistem skoring disfungsi organ pada sakit kritis, untuk memprediksi mortalitas pasien sepsis.Tujuan. Mengetahui faktor risiko usia, status gizi, dan skor PELOD terhadap mortalitas sepsis.Metode. Retrospektif analitik berupa data rekam medis pasien berusia 1 bulan – 18 tahun di PICU RSCM bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 14 publications
1
9
0
4
Order By: Relevance
“…This difference may have been due to their larger sample size of 209 subjects. 8 The PELOD-2 score analysis was also in line with…”
Section: Discussionsupporting
confidence: 60%
“…This difference may have been due to their larger sample size of 209 subjects. 8 The PELOD-2 score analysis was also in line with…”
Section: Discussionsupporting
confidence: 60%
“…A study in Jakarta stated the same results, which analyzed mortality in pediatric patients with sepsis and found out that the median age of subjects was 15 months (range 2-192) with the highest distribution in the 1 month -1 year age group (62%). 11 Younger age has been associated with immune system immaturity and is usually accompanied by comorbidities, such as congenital heart disease and kidney disease, thus the incidence of infections that cause sepsis is a factor that increases the risk of mortality. 1,[11][12][13] Also, the Sepsis Prevalence, Outcomes, and Therapies Study (SPROUT) conducted in 128 PICUs in 26 countries revealed that patients who met SIRS-severe sepsis criteria based on international consensus had a mean age of 3 years, and the foci of infection were the respiratory system (40%) and bacteremia (19%).…”
Section: Discussionmentioning
confidence: 99%
“…Saraswati et al showed that subjects with PELOD scores ≥ 20 had a 39.08 times higher mortality risk than subjects with PELOD score < 20. 17 In our study,of the 92 patients who underwent lactate examinations, only 58 had the complete examination data required to calculate PELOD scores. We found no association between PELOD score and lactate level in shock patients ( Table 4), similar to a study by Ismyet al 18 Therefore, lactate level didn't affect the severity of sepsis marked by PELOD scores.…”
Section: Discussionmentioning
confidence: 99%